2022
DOI: 10.3390/ma15093139
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Performance of Sound Absorbing Materials Produced from Wool of Local Mountain Sheep

Abstract: Wool of mountain sheep, treated nowadays as a waste or troublesome byproduct of sheep husbandry, was used for the production of sound-absorbing materials. Felts of two different thicknesses were produced from loose fibres. Additionally, two types of yarn, ring spun and core rug, were obtained. The yarns were used for the production of tufted fabric with cut and loop piles. During the examinations, basic parameters of the obtained materials were determined. Then, according to standard procedure with the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…According to Broda and coworkers [192], the coarse wool carpets produced by the tufted technique seem to be very good sound absorbents. The works of Kobiela-Mendrek and coworkers support the same assumption [193].…”
Section: Textile Productsmentioning
confidence: 72%
“…According to Broda and coworkers [192], the coarse wool carpets produced by the tufted technique seem to be very good sound absorbents. The works of Kobiela-Mendrek and coworkers support the same assumption [193].…”
Section: Textile Productsmentioning
confidence: 72%
“…The maximum SAC value of 0.56 exhibited best sound absorption at 2000 Hz for specimen of SG with its thickness of 10 mm coated with PAS of 1.0-mm diameter is similar to that for specimen of SG with its thickness of 20 mm coated with PAS of 1.5-mm diameter. This could be due to the sound waves absorbed by a low density of SG loosely packed together with a plenty of space transferred through a larger size of PAS hole is approximately similar to that absorbed by a high density of SG densely packed together with a limited space transferred through a narrow PAS hole size [ 2 ]. A difference in the SAC value of SG specimen coated PAS with the hole diameters each of 1.0, 1.5 and 2.5 mm at 2000 Hz could be more significant compared to that at the sound frequency of 125 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…The application of the natural materials attracted significant interest for more than a century could be due to the physical properties of natural plant fibers offer opportunity of sound absorbers potentially used in acoustic engineering to reduce noise pollution [ 1 ]. The manufacturing of natural materials possessed good absorption capacity could be similar to the commercial products usually made of the expensive synthetic materials used for the reduction of noise [ 2 ]. Noise pollution associated with several negative effects on both land and in the sea can cause health problems for people and wildlife, contributing to the cause of heart attacks affected an annoyance and sleep disturbance [ [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
“…High sound absorption capacity and extraordinary acoustic properties of wool felt have been long known and are commercially used in piano manufacturing. Kobiela-Mendrek et al were studied acoustic performance of sound absorbing properties of sheep wool materials produced by felting and tufting techniques (Broda et al , 2022). They concluded that acoustic properties of the produced materials depend on their structure and parameters.…”
Section: Introductionmentioning
confidence: 99%